How audit work experience affects perceptions towards roles and responsibilities of an auditor - Lai, Sing Wah (2008)
Perceptions towards roles and responsibilities of an auditor are investigated for the following three groups of respondents: Students who have not undergone Professional Attachment, Students who have undergone Professional Attachment and Professional Auditors. We hypothesized that with increasing work experience, respondents will perceive a more restricted role and less responsibilities for an auditor.